Raccoon-borne pathogens: Parasites - Caitlin Jarvis; Mathieu Basille (EDIS, 2020)
Diseases carried by northern raccoons present significant health hazards to both people and pets. This 7-page fact sheet written by Caitlin Jarvis and Mathieu Basille and published by the UF/IFAS Department of Wildlife Ecology and Conservation is part of a series addressing health hazards associated with raccoons. It describes the most important internal and external parasites associated with raccoons. Sick wild animals can act tame, but do not approach! Contact animal control or a wildlife rehabilitator if an animal seems to be behaving abnormally or if you suspect it is sick.